2009
DOI: 10.1128/jb.01074-08
|View full text |Cite
|
Sign up to set email alerts
|

The Leucine-Responsive Regulatory Protein, Lrp, Modulates Microcin J25 Intrinsic Resistance inEscherichia coliby Regulating Expression of the YojI Microcin Exporter

Abstract: Many Escherichia coli K-12 strains display an intrinsic resistance to the peptide antibiotic microcin J25. In this study, we present results showing that the leucine-responsive regulatory protein, Lrp, is involved in this phenotype by acting as a positive regulator of YojI, a chromosomally encoded efflux pump which expels microcin out of cells. Exogenous leucine antagonizes the effect of Lrp, leading to a diminished expression of the pump and an increased susceptibility to microcin J25.Microcin J25 (MccJ25) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…We have previously shown that yojI , an E. coli ORF with an unknown function, encodes an efflux pump that can use MccJ25 as a substrate (Delgado et al , 2005). In fact, YojI seems to be responsible for part of the intrinsic resistance shown by most E. coli strains to MccJ25 (Socías et al , 2009). Although the most likely explanation for the low activity of I13K, as compared with that of native MccJ25, would be a deficient uptake of the antibiotic, we investigated the possibility that both peptides enter cells to the same extent, but, once in the cytoplasm, the mutant peptide could be more efficiently pumped out than MccJ25 by YojI.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that yojI , an E. coli ORF with an unknown function, encodes an efflux pump that can use MccJ25 as a substrate (Delgado et al , 2005). In fact, YojI seems to be responsible for part of the intrinsic resistance shown by most E. coli strains to MccJ25 (Socías et al , 2009). Although the most likely explanation for the low activity of I13K, as compared with that of native MccJ25, would be a deficient uptake of the antibiotic, we investigated the possibility that both peptides enter cells to the same extent, but, once in the cytoplasm, the mutant peptide could be more efficiently pumped out than MccJ25 by YojI.…”
Section: Resultsmentioning
confidence: 99%
“…Microcin production by Gram-negative bacteria is typically triggered by environmental and nutritional factors (Duquesne et al, 2007 ). Examples include microcin B17, C, E492, and J25 that are regulated by a global regulator (e.g., OmpR and sigma factors), or in response to depletion of nutrient, carbon, and or nitrogen source (de Lorenzo, 1985 ; Moreno et al, 2002 ; Socias et al, 2009 ). Unlike bacteriocins from lactic-acid producing bacteria and for which quorum sensing (QS) is known to play a regulatory role (Drider et al, 2006 ), to date there have been no reports about the contribution of QS to the regulation of Class I, IIa, or IIb microcin expression.…”
Section: Discussionmentioning
confidence: 99%
“…[148, 149] YojI, an ABC exporter, functions with TolC and mediates resistance to microcin J25[150] and its expression is modulated by the leucine-responsive regulatory protein (Lrp). [151] Preincubation of FloR pump-producing florfenicol-resistant strains with anti-FloR antibody, in the presence of lysozyme and ethylenediaminotetraacetic acid, increased the intracellular accumulation of florfenicol. [152] A paired SMR pump, MdtJI, exports spermidine.…”
Section: Drug Efflux In Gram-negative Bacteriamentioning
confidence: 99%